Flexural behavior of reinforced concrete beams repaired with ultra-high performance fiber reinforced concrete (UHPFRC) - Safdar, Muhammad; Matsumoto, Takashi; Kakuma, Ko (Composite structures, 2016)
Over the past few decades, premature deterioration of reinforced concrete structures exposed to severe environmental actions and mechanical loading has become a serious problem. Previous studies have shown that the use of ultra-high performance fiber reinforced concrete (UHPFRC) improves the structural response and extends the durability of concrete structures. In this study, the flexural behavior of reinforced concrete beams retrofitted with UHPFRC is investigated and experimental results are compared with 3-D finite element analysis. The experiments were performed on reinforced concrete beams repaired in tension and compression zone, with UHPFRC of varying thicknesses. The flexural strength of repaired beams was investigated by four-point bending test and compared with that of reference beam without repair. Experimental and analytical results indicate that the ultimate flexural strength of RC beams repaired with UHPFRC in tension and compression zone is increased, with the increase of UHPFRC thickness. Thereafter, a parametric study was carried out by using MSC/Marc simulation to investigate the influence of tensile properties of UHPFRC and yield strength of tension steel on the flexural capacity of repaired beams. The investigation shows that the UHPFRC improves stiffness and delay the formation of localized cracks, thus, improving the resistance and durability of repaired beams.